The Effect of Financial Compensation and Motivation on Performance with Gender Equality as The Moderating Variable in The Regional Secretariat of East Java Province: The Study of Non-Permanent Employees with Work Agreements - Arum Dwi Rachma* (Universitas Airlangga, 2019)
The Role of Non-Permanent Employees with Work Agreements was very important to support the achievement of the vision and mission of an organization. Performance evaluation of Non- Permanent Employees with Work Agreements assessed by the direct supervisor consisted of several aspects, namely integrity, discipline. service orientation, cooperation, and coordination and the performance results of some employees were still relatively low. The low performance could be caused by several factors one of which was financial compensation and motivation owned by employees. Besides, to improved employee performance, gender equality in an organization also needs to be considered. This was because, in the absence of gender differences in an organization, it was easier to achieve high levels of performance. The purpose of this study was to identifying and analyzing the effect of financial compensation and motivation on the performance of Non-Permanent Employees with Work Agreements with gender equality as a moderating variable in the Regional Secretariat of East Java Province. This research used a quantitative approach combined with an explanatory method design. The results of this study concluded that: 1.) Financial compensation had a positive and significant effect on performance;2.) Motivation had a positive and significant effect on performance; 3.) Gender equality had a positive and significant effect on performance; 4.) Financial compensation and motivation had a positive and significant effect on the performance of Non-Permanent Employees with Work Agreements with gender as a moderating variable in the Regional Secretariat of East Java Province.